Electrocution Deaths in Northwest Delhi, India: A Five-Year Retrospective Analysis (2018–2022) - Naresh Jeengar; Chaitanya Mittal; Suraj Sundaragiri; Upender Kishore (Indian Journal of Forensic Medicine and Pathology, 2025)
Introduction: Electricity is an essential resource in modern society. However, its ubiquitous presence also presents inherent risks to human life. Although electrocution deaths account for a small proportion of overall fatalities, which can be preventable, which represents a signi𿿿cant public health concerndue toaccidental exposure, equipment malfunction, and failure to use proper safety precautions. Objective: To analyze the demographic pro𿿿le, seasonal variation, occupation, and forensic characteristics of electrocution deaths in Northwest Delhi, India, over 𿿿ve years. Methods: A retrospective review was conducted on 105 autopsy-con𿿿rmedelectrocution death cases from the Department of Forensic Medicine at Dr. Babasaheb Ambedkar Medical College, Rohini, Delhi (2018–2022). Results: Electrocution fatalities accounted for approximately 1.2% of all autopsy cases. Males predominated (95 cases, 90.5%), with the most affected age group being 21–30 years (40 cases, 38.1%), followed by 11–20 years (26 cases, 24.8%) and 31–40 years (21 cases, 20.0%). Cases peaked during the monsoon season (June–September; 73 cases, 69.5%), with the highest incidence observed between 12:00 PM and 5:00 PM (41 cases, 39.0%). The labor class represented the most common occupational group (24 cases, 22.9%), and the most common source of electrocution was the exposed electric wires and faulty electrical boards (18 cases, 17.1%). Upper extremity involvement was most frequent (73 cases, 69.5%), with entry wounds identi𿿿ed in 92 cases (87.6%) and both entry and exit wounds observedin7 cases (6.7%). Conclusion: The study indicates that electrocution deaths in the Northwest region of Delhi are predominantly due to accidents and occur most often in young males, particularly during the monsoon season and afternoon hours. So, several preventative strategies including improved electrical safety education, regular maintenance of electrical installations, and heightened public awareness are essential to reduce these fatalities.